Tunable polymer/liquid crystal composite devices - Liu, Yanjun (2008)
This thesis focused on developing new electro-optical devices based on PDLC or H-PDLC. In particular, we firstly optimized the fabrication conditions for H-PDLC Bragg gratings. Using holography, one-dimensional (1D) H-PDLC Bragg grating was fabricated. The 1D H-PDLC grating itself is a 2 ? 2 optical switch. With optimization of the fabrication parameters, we obtained a polarization insensitive H-PDLC optical switch with high contrast ratio (23.4 dB), high signal-noise ratio (15.1 dB), and fast response time (200 ?s).